Ameliorative Effects of Daphnopsis costaricensis Extract against Oxazolone-Induced Atopic Dermatitis-like Lesions in BALB/c Mice - Bae, Yunji; Kim, Taeyoung; Park, Nojune; Choi, Sangho; Yi, Dongkeun; Soto, Silvia; Zamora, Nelson; Kim, Sunam; Yang, Minhye (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The genus Daphnopsis has been traditionally used as a purgative, diuretic, stimulant, and psoriasis treatment. In this study, the anti-AD (atopic dermatitis) activities of the Daphnopsis costaricensis EtOH extract (DCE) were investigated in an oxazolone (OX)-induced mouse model of AD, and the anti-inflammatory effects of its active compounds were confirmed in PI-sensitized or IgE/DNP-BSA-sensitized RBL-2H3 cells. DCE improved the symptoms of OX-induced inflammatory dermatitis (swelling, erythema, and increased ear thickening) in OX-induced BALB/c mice ears and reduced epidermal thickness and mast cell infiltration. Eleven flavonoid compounds were isolated from DCE, and two compounds (7,8-dimethoxyflavone and 7,2'-dimethoxyflavone) significantly inhibited IL-4 overexpression in PI-induced RBL-2H3 cells and mast cell degranulation in IgE + DNP-BSA-induced RBL-2H3 cells. Our study indicates that DCE and two compounds (7,8-dimethoxyflavone and 7,2'-dimethoxyflavone) might effectively improve inflammatory and atopic skin symptoms.